Re: Maxillofacial Surgery and COVID-19, the Pandemic! - Jayasuriya, Nadeena Sri Swarnagupta (J Maxillofac Oral Surg, 2020)
COVID-19 pandemic revolutionised the practice of oral & maxillofacial surgery in addition to almost all specialties in health care across the globe. Stringent infection control is the cornerstone in this regard. However, there are some hidden benefits of COVID-19 lockdown and social distancing in reducing the incidence of maxillofacial trauma.